Styling your writing mixing and matching academic writing techniques to create something uniquely you - McConnel, Jen (English professor) (New York, NY : Routledge, 2022)
This text helps developing writers in the academy and beyond think through their writing process and develop strategies for styling their writing to meet the demands of a wide range of goals. The book imagines writing as an assortment of "outfits"-- bundles of styles and strategies through which one approaches a writing purpose, such as writing focused on experimentation and growth or writing focused on a professional task. By assessing the outfits writers feel most and least confident in, and examining how to be more at home in the outfits that matter to them, this book helps students develop both specific skills and their overall identity as writers. Readers are guided through before-, during-, and after-writing strategies and techniques, including: freewriting, outlining, visual planning, and composing in multimodal forms. Readers are also introduced to the importance of setting clear writing goals and sharing their work in a variety of ways, both in preparation for classroom success through peer review and writing center visits, and beyond the classroom in virtual and in-person spaces. This book serves as a core or supplemental text for writing courses at the undergraduate, graduate, or high school level, or as a writing guide for individual readers.
Keywords: LANGUAGE ARTS & DISCIPLINES / Composition & Creative Writing; Academic writing; English language -- Composition and exercises -- Study and teaching (Higher); Language arts (Higher)